Research on the effect of digital economy on new agricultural productivity - Pengfei, Zhou; Yang, CAI; Xianfeng, Li (Asian Journal of Economics and Empirical Research, 2024)
This article comprehensively explores the impact of the digital economy on the new quality of agricultural productivity. Leveraging the panel data of 31 provincial-level regions in China from 2011 to 2022, a series of advanced econometric models, such as bidirectional fixed-effect, intermediary effect, threshold effect, and spatial Durbin models, are established for in-depth empirical analysis. The results are multi-faceted. Firstly, the digital economy significantly elevates the new quality of agricultural productivity, yet with temporal and regional variances. Secondly, it acts as a catalyst for productivity growth by augmenting government revenue, spurring technological innovation, and enriching human capital. Thirdly, rural education, the urban-rural information chasm, and information infrastructure construction exert distinctive threshold effects on this promotional process. Notably, a significant spatial spillover effect exists. Consequently, based on these findings, suggestions for bolstering the new quality agricultural productivity are proffered from four perspectives: government governance, policy formulation, digital infrastructure construction, and human capital enhancement.